Influence of Working Conditions on Parameters of Thermoacoustic Engine with Travelling Wave - Andrzej Bogdan DOBRUCKI; Bartłomiej KRUK (Archives of Acoustics, 2020)
Thermoacoustic converters are devices for direct conversion of acoustic energy into thermal energy in the form of temperature difference, or vice versa – for converting thermal energy into an acoustic wave. In the first case, the device is called a thermoacoustic heat pump, in the second – thermoacoustic engine. Thermoacoustic devices can use (or produce) a standing or travelling acoustic wave. This paper describes the construction and properties of a single-stage thermoacoustic engine with a travelling wave. This kind of engine works using the Stirling cycle. It uses gas as a working medium and does not contain any moving parts. The main component of the engine is a regenerator equipped with two heat exchangers. Most commonly, a porous material or a set of metal grids is used as a regenerator. An acoustic wave is created as a result of the temperature difference between a cold and a hot heat exchanger. The influence of working gas, and such parameters as static pressure and temperature at heat exchanger on the thermoacoustic properties of the engine, primarily its efficiency, was investigated. The achieved efficiency was up to 1.4% for air as the working medium, which coincides with the values obtained in other laboratories. The efficiency for argon as working gas is equal to 0.9%.